Improved Superconducting Magnetic Energy Storage (SMES) Controller for High Power Utility Applications - Molina, Marcelo Gustavo (2011)
Superconducting magnetic energy storage (SMES) systems are getting increasing interest in applications of power flow stabilization and control in the transmission network level. This trend is mainly supported by the rising integration of large-scale renewable energy power plants into the high-power utility system and by major features of SMES units. In a SMES system, the power conditioning system (PCS) is the crucial component for controlling the power exchange between the superconducting coil and the ac system. The dynamics of the PCS directly influences the validity of the SMES in the dynamic control of the power system. This paper describes a novel PCS scheme of SMES to simultaneously perform both active and reactive power flow controls. Moreover, a detailed model of the SMES unit is derived and a three-level control scheme is designed, comprising a full decoupled current control strategy in the dq reference frame with a novel controller to prevent PCS dc bus capacitors voltage drift/imbalance. The dynamic performances of the proposed systems are fully validated by computer simulation.